Knowledge, attitude and practice towards disaster preparedness among Emergency Department medical personnel in Malaysia - Amran, Dora Natasha (2020)
Introduction Disasters are phenomenon that causes damage in properties and lives. Disaster preparedness is an action to be taken into systematic planning with regards to disaster. Objective of this study is to determine the level of knowledge, attitude and practices (KAP) among ED medical personnel in Malaysia in disaster preparedness and to study the associated factors between the different level of knowledge, attitude and practices among ED medical personnel Methodology This cross-sectional study was conducted in 12 hospitals in Peninsular Malaysia which were randomly selected. A self-administered questionnaire regarding the knowledge, attitude and practices towards disaster preparedness comprise of 37 questions were used. A total of 427 participants were recruited. This study was carried out for one year from March 2019-March 2020. Results This study showed that emergency medicine staff personnel in Malaysia had adequate knowledge, attitude and practice towards disaster preparedness which score 91.6%,78.2% and 61.1% respectively. Experience and training in disaster response were significant predictors associated with increased level of knowledge and practice. Duration of working experience was also associated with increased level of practice. However, there were no significant association found with level of attitude and disaster preparedness. Conclusion The level of knowledge, attitude and practice was satisfactory in ED medical personnel. Curriculum on theories and practices of disaster preparedness should be incorporated to mentally prepare emergency department staff in the event of disaster. Continuous education and training of staff is important to improve the healthcare system.